Mathematical Modeling and Dynamic System in Epidemiology - Bhatta, Raghu Bir; Rijal, Bikash (AMC Journal (Dhangadhi), 2024)
Pandemics have been happening on the planet since the days of yore. It is troublesome in the old pandemics however pandemics of the later beginning have passed on certain messages. These significant examples ought to be acknowledged sincerely for confronting all the more skillfully in the accompanying pandemics. They have raised a ruckus around town since early times. It has been found that Nepal did not have connectivity with the pandemics in the past. It is only in the Corona pandemic that Nepal has also been a part of the whole globe. Our investigation focuses on historical aspects of bio-epidemiological mathematical surveys. Historical background of epidemics, their parallel situation in Nepal, and their correlation with mathematical modeling have been provided. Different dynamical systems used in epidemiology are mentioned. This study has also emphasized on deterministic modeling, and different disease transmission rates applied to the population dynamics of infectious diseases.